PENGARUH PENGGUNAAN MEDIA KARTU MOTIF GORGA TERHADAP KEMAMPUAN MENGHITUNG NILAI TEMPAT BILANGAN SISWA KELAS II SD NEGERI 060910 MEDAN - Fuji Chintya; Elvi Mailani; Fahrur Rozi; Winara; Nur Hudayah M (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using Gorga motif card media on students’ ability to calculate place value in grade II of SD Negeri 060910 Medan. This research used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 56 students divided into experimental and control classes. Data were collected using tests and analyzed with an independent sample t-test. The results showed a significance value (Sig. 2-tailed) of 0.016 < 0.05, indicating a significant effect of the use of Gorga motif card media on students’ ability to calculate place value. In addition, the use of culture-based media makes learning more meaningful and improves students’ understanding. Thus, the Gorga motif card media is effective in improving mathematics learning outcomes.